Perceptions of organ donation by elderly community members in a rural community of Sekhukhune District, Limpopo Province - Moropa, Monareng (My University, 2019)
Demographical factors affect the way people perceive, conceptualise and make meaning of their daily living experiences, which in turn influence their decision-making abilities in certain situations. Therefore, perceptions and conceptualisations, together with the associated attitudes to organ donation, were defined and understood in participants’ socio-cultural context. A qualitative study was conducted among the African elderly community members of Madibaneng Village (Sekhukhune District), Limpopo Province (South Africa) to explore perceptions of organ donation. African elderly community members were selected using purposive sampling, after ethical clearance from the University and gate-keepers’ permission from the Tswako-Lekentle traditional council had been obtained. Six (6) males and six (6) females were interviewed. Data was collected using semi-structured interviews and analysed using the thematic analysis method. The following psychological themes and subthemes emerged from the study: African elderly community members’ understanding and knowledge about organ donation (inadequate knowledge and lack of awareness); community members’ feelings about organ donation; African elderly community members attitudes to organ donation (family dynamics relating to organ donation, culture and organ donation and psychological aspects of organ donation), and participants’ perceptions of those living with donated organs. The findings revealed that multiple demographical factors affect and influence people’s perceptions of organ donation. The study revealed that 80% of the elderly community members expressed some positive perceptions about the process of organ donation; however, some of the participants expressed conflicting factors that might affect their ultimate decision about becoming donors, such as associated psychological aspects. Other participants portrayed a negative perception that was more likely to have been affected by cultural factors, their family dynamics, belief systems and other social factors in their context. The findings from the current study emphasise that there is a need for effective awareness campaigns to curb the levels of illiteracy and inadequacy in knowledge concerning the subject of organ donation and to incorporate the demographical factors of particular social contexts in the healthcare system and related policies.
Thesis (M. A. (Clinical Psychology)) -- University of Limpopo, 2019
Keywords: Organ donation; Elderly; African elderly; Donation of organs, tissues, etc.; Older people; Rural elderly